Regulatory novelty after financial crises: Evidence from international banking and securities standards, 1975–2016. Issue 3 (18th July 2020) - Pagliari, Stefano; Wilf, Meredith
Abstract: Financial crises are often presented as triggers for important innovations in international regulation of financial markets, but existing evidence for this claim primarily derive from the analyses of individual initiatives, assessed against noncomparable benchmarks. In order to provide systematic evidence of financial crises' impact on international financial regulatory change, this paper develops a novel text‐as‐data approach to measure regulatory novelty. We use this approach to analyze the full population of international banking and securities standards between 1975 and 2016. Contrary to theoretical expectations, our empirical findings indicate rules designed by international banking and securities regulators following financial crises are on average as likely to build on existing international regulations as those designed before a crisis. We also find that international banking rules published after the 2008 Global Financial Crisis are an important exception.